Absolute parameters of young stars: HX Velorum. Issue 1 (6th May 2019) - Blackford, M G; Erdem, A; Sürgit, D; Özkardeş, B; Budding, E; Butland, R; Demircan, O
Abstract: We present combined photometric and spectroscopic analyses of the southern multiple star HX Vel. High-resolution spectra of this system were taken at the University of Canterbury Mt. John Observatory in the years 2009–2015. Absolute parameters for HX Vel tend to confirm its young and near-main-sequence nature. We specify the main adopted parameters of the (non-eclipsing) close binary as follows: M 1 = 8.5 ± 1.7, M 2  = 5.4 ± 1.2, R 1  = 5.0 ± 0.3, R 2  = 3.1 ± 0.2, (⊙); T 1 25 000 ± 1300, T 2 20 000 ± 2500 (K); systemic MV –4.2 ± 0.2. These parameters are sensitive to the low inclination, where we find a small disparity between the photometrically optimal 28 ± 2° and an adopted value of 26° that gives better consistency with main-sequence stellar modelling. The relationship of HX Vel to the galactic cluster IC 2395 and OB association Vela OB1C is also considered, in the context of photometric parallaxes found for HX Vel and other cluster members.